Caracterização e utilização de pó-de-pedra em revestimentos para restauração de edificações históricas em estilo art déco - Gizela Barbosa do Nascimento (2008)
In the decades of 30 and 40, the architectural style called art déco took place in many brazilian urban centers. It was based on a new technical and formal language, exploring the symmetry, straight lines, horizontality, ornamental cleaning, soberness and monumentality. This style set common the reinforced concrete application and the use of the stone dust covering in many façades, that nowadays have some pathologies and need restoration works. Therefore, this research analyses the stone dust mortar restoration techniques applied on Thibau Building façade, an art déco construction from 1943, placed at Belo Horizonte city. In order to evaluate the covering performance after its restoration, were done mortar characterization tests in the hardened condition and related to the mortar-substrate conditions. Concerning the axial compression tests, good results were obtained comparing to other researches, and regarding the pull-off strength values, the façade covering was approved. The water permeability test indicated that there isnt a standard performance at the building. The granulometry and the specific mass tests were used to characterize the mortar components. The chemical/mineralogical characterization, by means of X-rays fluorescence spectrometry, showed a big concentration of calcium, magnesium and oxygen at the stone dust, and, by means of X-rays diffraction, showed a big presence of dolomite crystalline peaks. It was also possible to conclude that the stone dust of the studied mortar is essentially used as a mineral addition.